Non-alcoholic fatty liver disease as metabolic consequence of obstructive sleep apnea - Ninić, Ana; Zdravković, Marija; Radosavljević, Vojislav; Gardijan, Vera; Memon, Lidija; Vekić, Jelena; Spasojević-Kalimanovska, Vesna (Archives of Pharmacy, 2020)
Obstructive sleep apnea (OSA) as a worldwide prevalent condition carries risk for cardiovascular and metabolic diseases, ultimately increasing overall mortality rates. Non-alcoholic fatty liver disease (NAFLD) can be considered as the primary metabolic disease, but also as a coexisting OSA comorbidity. Although prevalence of NAFLD covers quarter of world population, it increases with OSA presence. It can be speculated that chronic intermittent hypoxia (CIH) and sympathetic nervous system overactivity are involved in NAFLD pathogenesis and progression from simple steatosis through steatohepatitis to fibrosis. CIH provides the environment for liver oxidative stress, inflammation and increases the expression of genes involved in cholesterol and fatty acids synthesis. Catecholamines increase β-oxidation in liver and release free fatty acids from adipose tissue in plasma which inhibit insulin effects. Obesity and insulin resistance as key players in NAFLD development and advancement, deepen vicious circle of oxidative stress, inflammation and dyslipidemia. If not treated, OSA in NAFLD patients has been associated with inflammation, hepatocytes’ necrosis, and fibrosis. Continuous positive airway pressure (CPAP) represents gold standard for OSA therapy, allowing the unimpeded air passage through upper parts of respiratory system. However, it has been demonstrated that CPAP therapy have beneficial effects on cardiometabolic outcomes and slow liver degeneration.
Keywords: obstructive sleep apnea; chronic intermittent hypoxia; non-alcoholic fatty liver disease; fibrosis